2017
DOI: 10.18632/oncotarget.22957
|View full text |Cite
|
Sign up to set email alerts
|

Somatic mutation dynamics in MDS patients treated with azacitidine indicate clonal selection in patients-responders

Abstract: Azacitidine (AZA) for higher risk MDS patients is a standard therapy with limited durability. To monitor mutation dynamics during AZA therapy we utilized massive parallel sequencing of 54 genes previously associated with MDS/AML pathogenesis. Serial sampling before and during AZA therapy of 38 patients (reaching median overall survival 24 months (Mo) with 60% clinical responses) identified 116 somatic pathogenic variants with allele frequency (VAF) exceeding 5%. High accuracy of data was achieved via duplicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Recently, analysis of clonal selection under AZA treatment before allogeneic stem cell transplantation (allo‐SCT) confirmed that AZA could select mutated clones and showed that recurrent clones could re‐emerge at relapse. Other studies established that AZA may influence variant allele frequencies in MDS patients . Nevertheless, these studies suggested a limited selectivity of AZA treatment.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Recently, analysis of clonal selection under AZA treatment before allogeneic stem cell transplantation (allo‐SCT) confirmed that AZA could select mutated clones and showed that recurrent clones could re‐emerge at relapse. Other studies established that AZA may influence variant allele frequencies in MDS patients . Nevertheless, these studies suggested a limited selectivity of AZA treatment.…”
Section: Discussionmentioning
confidence: 89%
“…Other studies established that AZA may influence variant allele frequencies in MDS patients. 31 Nevertheless, these studies suggested a limited selectivity of AZA treatment. Usual response criteria and outcome could be improved by monitoring clonal selection under AZA treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study we summarized the results of 12 studies with whole exome/genome sequencing in MDS [10,11,[13][14][15][16][17][18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%